2011
DOI: 10.1210/en.2011-1039
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Controls Photoperiodic Changes in Tanycyte Vimentin and Neural Cell Adhesion Molecule Expression in the Djungarian Hamster (Phodopus sungorus)

Abstract: The Djungarian hamster displays photoperiodic variations in gonadal size synchronized to the seasons by the nightly secretion of the pineal hormone melatonin. In short photoperiod (SP), the gonads regress in size, and circulating sex steroids levels decline. Thus, the brain is subject to seasonal variations of both melatonin and sex steroids. Tanycytes are specialized glial cells located in the ependymal lining of the third ventricle. They send processes either to the meninges or to blood vessels of the medio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…The basis for this conclusion is that previous studies in Siberian hamster have shown how cells immunopositive for vimentin project radially from tanycytes into the medial basal hypothalamus, although the extent of the radial projections are photoperiod-dependent, with long projections under LD, which decrease or disappear under SD20. Other work undertaken in hamsters and sheep has also shown morphological changes in the hypothalamus that are associated with changes in photoperiod14161819. Thus, the increased vimentin immunolabelling of projections from the tanycytes and ependymal cells of the HVZ of SD-housed F344 rats in response to 2 week infusion of chemerin mimics a LD response.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The basis for this conclusion is that previous studies in Siberian hamster have shown how cells immunopositive for vimentin project radially from tanycytes into the medial basal hypothalamus, although the extent of the radial projections are photoperiod-dependent, with long projections under LD, which decrease or disappear under SD20. Other work undertaken in hamsters and sheep has also shown morphological changes in the hypothalamus that are associated with changes in photoperiod14161819. Thus, the increased vimentin immunolabelling of projections from the tanycytes and ependymal cells of the HVZ of SD-housed F344 rats in response to 2 week infusion of chemerin mimics a LD response.…”
Section: Discussionmentioning
confidence: 91%
“…In the Syrian hamster ( Mesocricetus auratus ), BrdU incorporation into tanycytes, as a marker for cell proliferation, is affected by photoperiod18 and equally in F344 rats and sheep more cells are generated in SD as compared to LD1517. In Siberian hamsters ( Phodopus sungorus ) and sheep, adaptations of neural pathways as well as cell structure and morphological changes in the hypothalamus are also associated with changes in photoperiod14161920. Taken together these data suggest that structural changes within the hypothalamus may be at the core of the long-term effects of photoperiod on physiology, such as regulation of energy balance and body weight.…”
mentioning
confidence: 99%
“…If PSA is enzymatically removed from neural-cell adhesion molecule (NCAM) in the hypothalamus, HFD induced modifications in metabolic circuits can be blocked and the adaptation to HFD-induced hyperphagia attenuated (385). In addition, studies in photoperiodic models have shown that PSA and NCAM levels in tanycytes are reduced during short photoperiods in conjunction with vimentin levels, modulating the plasticity for tanycyte connections with arcuate neurons (387). …”
Section: Functions Of Non-neuronal Cellsmentioning
confidence: 99%
“…Successful treatment of SAD with bright light therapy, suggests that prolonged melatonin signals after waking contribute to depressive symptoms [18,19]. Individuals with SAD display prolonged periods of elevated melatonin during the winter relative to the summer, similar to changes observed in animals that use photoperiod to time reproduction [18,22,23]. Nondepressed individuals did not display seasonal differences in circulating melatonin concentrations, suggesting a role for melatonin in SAD etiology [18].…”
Section: Introductionmentioning
confidence: 99%